Improving Seventh Grade Students' Ability to Write Procedural Texts through the Implementation of the Project Based Learning (PjBL) Model - Hanifah Parapat; Lili Herawati Parapat (PANTAK: Jurnal Penelitian Tindakan Kelas, 2026)
This study aimed to improve seventh-grade students' ability to write procedural texts through the implementation of the Project Based Learning (PjBL) model. The research employed Classroom Action Research (CAR) based on the model of Kemmis and McTaggart, consisting of two cycles: planning, acting, observing, and reflecting. The participants were 30 seventh-grade students at a junior high school. Data were collected through writing tests, classroom observations, interviews, field notes, and documentation. Quantitative data were analyzed using descriptive statistics by calculating the students' mean scores and the percentage of students achieving the Minimum Mastery Criterion (KKM), while qualitative data were analyzed through data condensation, data display, and conclusion drawing. The findings revealed a significant improvement in students' writing ability throughout the research. The mean score increased from 61.83 in the pre-test to 72.47 in Cycle I and 82.93 in Cycle II. Likewise, the percentage of students achieving the KKM increased from 26.67% in the pre-test to 63.33% in Cycle I and 86.67% in Cycle II. The qualitative findings also indicated that students became more active, motivated, collaborative, and confident during the learning process. They demonstrated better understanding of the generic structure and language features of procedural texts and were more engaged in planning, drafting, revising, and presenting their writing projects. The study concludes that the implementation of the Project Based Learning (PjBL) model effectively improves seventh-grade students' ability to write procedural texts while simultaneously enhancing their classroom participation and learning motivation. Therefore, Project Based Learning is recommended as an effective student-centered instructional model for teaching writing, particularly procedural texts, in junior high schools.